Strategi Pengembangan Pembelajaran Berbasis Teknologi dalam Pendidikan Agama Islam - Thiara Deah Lestari; Desy Eka Citra Dewi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the strategic role of Islamic Religious Education (PAI) in shaping students’ character, morals, and spirituality, enabling them to become faithful, devout, and noble individuals amidst the challenges of globalization and technological advancement. A qualitative literature-based approach was employed, synthesizing relevant theoretical frameworks and empirical studies on PAI learning systems, teacher empowerment, and character education in the digital era. The findings reveal that the IRE learning system faces significant challenges in adapting to digital developments without compromising core Islamic values. Improving spirituality and morality through PAI is identified as a long-term solution for producing graduates with strong character, responsibility, and inner peace. Achieving this requires professional, innovative teachers capable of integrating multicultural values, technology, and humanistic approaches into the learning process. Teacher empowerment emerges as a crucial strategy for enhancing pedagogical, professional, social, and personal competencies to enable optimal performance. This study uniquely synthesizes the intersection of digital adaptation, multicultural integration, and humanistic pedagogy within PAI teacher empowerment frameworks. Findings emphasize the need for structured professional development programs that equip PAI teachers with digital literacy, multicultural competence, and humanistic teaching skills. This research contributes a conceptual framework for strengthening PAI teacher capacity, offering actionable insights for policymakers and educational institutions in designing empowerment strategies that balance technological innovation with Islamic values preservation.